Spiral periodic structure inside chaotic region in parameter-space of a Chua circuit - Rech P.C.* (2012)
In this letter we investigate, via numerical simulations, the parameter-space of the set of autonomous first-order differential equations of a Chua circuit. We show that this parameter-space presents self-organized periodic structures immersed in a chaotic region, forming a single spiral structure that coils up around a focal point. Additionally, bifurcation diagrams are used to show that those periodic structures also organize themselves in period-adding cascades, along specific directions that point towards this same focal point. Copyright © 2010 John Wiley & Sons, Ltd.